2012
DOI: 10.1016/j.prostaglandins.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neutral ceramidase increases inflammation in a mouse model of inflammatory bowel disease

Abstract: Sphingolipids are emerging as important mediators of immune and inflammatory responses. We have previously demonstrated that sphingosine-1-phosphate (S1P) and its synthetic enzyme sphingosine kinase-1 (SK1) play an important role in inflammatory bowel disease. S1P generation is dependent on SK phosphorylation of sphingosine. Generation of sphingosine results only from the breakdown of ceramide by ceramidases (CDase). In this study, we set out to determine the role of neutral CDase (nCDase) in S1P generation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 41 publications
(51 reference statements)
3
50
0
Order By: Relevance
“…This in turn resulted in S1P elevation. These results suggest that NC may protect against inflammation (Snider et al, 2012). …”
Section: Neutral Ceramidase (Asah2 Asah2b Asah2c)mentioning
confidence: 84%
“…This in turn resulted in S1P elevation. These results suggest that NC may protect against inflammation (Snider et al, 2012). …”
Section: Neutral Ceramidase (Asah2 Asah2b Asah2c)mentioning
confidence: 84%
“…Additionally, the role of ceramidases in UC has recently been investigated. These studies, however, have found that despite the expression of neutral CDase and alkaline CDase 3 in the intestinal mucosa, these enzymes do not contribute to S1P-mediated inflammation and actually may have a protective role in UC (Fig 1) (Snider et al, 2012; Wang et al, 2016). Thus it remains inconclusive which sphingolipid enzymes and metabolites function in connection to drive particular mechanistic signatures of inflammation in UC.…”
Section: Bioactive Sphingolipid Signaling In Ulcerative Colitismentioning
confidence: 94%
“…Kono et al (2006) demonstrated that loss of nCDase activity impairs the intestinal degradation of ceramide, and suggests that nCDase is a key enzyme in the catabolism of dietary sphingolipids and regulates of the cellular levels of ceramide and sphingosine in the gastrointestinal tract. Additionally, Snider et al (2012) recently reported that, under inflammatory bowel disease conditions, loss of nCDase activity results in an unexpected increase in both S1P generation and inflammatory responses, and suggests that nCDase may play a protective role in regulating inflammation and S1P levels.…”
Section: Ceramidases and Their Role In Regulating Cellular Responsesmentioning
confidence: 99%